Timing jitter reduction of passively mode-locked fiber laser with carbon nanotube saturable absorber by optimization of cavity loss - Wu, Kan (2013)
We investigate the relationship between timing jitter and cavity loss of a passively mode-locked fiber ring laser with carbon nanotube as saturable absorber. It is the first time that we experimentally demonstrated the reduction of timing jitter by properly increasing laser cavity loss. The lowest timing jitter is achieved when the cavity loss is optimized. Theoretical analysis is in agreement with the experimental observations on the effect of cavity loss for the reduction of timing jitter. Moreover, it is experimentally shown that, at an optimal value of cavity loss, the timing jitter is reduced significantly by 24%, while the relative intensity noise increased by 4% only.